Conceptual Issues and Challenges in IFRS Research : Towards a Comprehensive Research Framework - Kulkarni, Prasanna; Aanand, Shubhra (Indian Journal of Finance, 2017)
International Financial Reporting Standards (IFRS) constitute a comprehensive set of accounting standards, formulated for harmonization and unification of global accounting practices ; 119 out of 143 jurisdictions require IFRS for most domestic publicly accountable entities (listed companies and financial institutions) in their capital markets. IFRS was adopted in most of Europe and Australia from 2005. Other countries have also started adopting IFRS since then. Some countries have opted for â€œconvergenceâ€ - adoption with modifications for merging with domestic standards. Some companies (particularly those listed on stock exchanges) have adopted IFRS voluntarily. IFRS implementation is jointly regulated by the government, professional accounting bodies, and the regulator for securities within the jurisdiction. Extensive global research is being conducted to measure the impact of IFRS on companies, managers, investors, and their economic and financial implications. Research on IFRS implementation is conducted as post - implementation as empirical data keeps coming in. There is great diversity in IFRS research. Apart from regulators and professional accounting bodies, the researchers are academicians, professional practitioners, and consulting firms providing IFRS consultation. Corporate management, economic/legal institutions, and local government are interested in such research. An individual IFRS researcher may or may not be aware of related theoretical paradigms. This paper discussed the main paradigms and related conceptual issues for the benefit of new researchers and existing researchers already working with particular research designs or tools. This paper also brought out a comprehensive research framework for IFRS research, which should be useful for choosing the correct approach and consequently, the relevant design, methodology, and tools.